Patellofemoral Joint Loading During Bodyweight One-Legged and Two-Legged BOSU and Floor Squats - Rafael Escamilla; Naiquan Zheng; Toran D. MacLeod; Rodney Imamura; Kevin E Wilk; Shangcheng Wang; Robert Asuncion; Irwin S. Thompson; Arnel L. Aguinaldo; Glenn S Fleisig (International Journal of Sports Physical Therapy)
# Background